Construção e validação do instrumento prevenção de lesão por pressão na pediatria - Ferreira, Mayara Kelly Moura (2018)
Hospitalization involves risks that may compromise the child's safety during hospitalization, because of the complexity of health care adverse events may occur. Among the adverse events of health care, we highlight the occurrence of pressure injury. The aim of this study was to construct and validate an instrument for the prevention of pressure injury in pediatrics. Methodological study developed in three stages : 1st stage - Construction of the measurement instrument, developed from the verification items proposed by the Protocol for the prevention of pressure ulcer of the Ministry of Health; 2nd stage - Evaluation of psychometric properties, in which it was performed: 1) Validity of content with evaluation of seven specialists through ICC; 2) Construct validity from the factorial analysis and contrasted group, performed with 235 nursing professionals involved in direct child care in three hospitals in the city of Fortaleza, Ceará; and 3) Reliability (Cronbach's alpha), also performed with the same 235 professionals; Step 3 - Identification of actions performed by nursing professionals in pressure injury prevention. As a result, in the first stage, the first version of the instrument was obtained, entitled Pressure ulcer prevention in pediatrics (PUPP), composed of 24 items distributed in seven domains. In the second stage, in the validation of content, the instrument achieved a general ICC of 0.983, an ICC of 0.954 for simplicity, 0.945 for clarity and 0.955 for relevance, obtaining the 2nd version of the instrument, entitled Prevention of pressure injury in pediatrics (PLPP), formed by 23 items. Factor analysis revealed the presence of three domains. There was a statistically significant positive association between prevention of pressure injury and the adult age range (31 to 40 years), participation of improvement courses and absence of attrition at work. Cronbach's alpha (0.938) showed that the instrument is reliable. In the third stage, the performance of the professionals was analyzed by the positivity index (PI) and it was identified that in no action the assistance was considered desirable, three actions obtained IP consistent with a safe assistance, only in one action the assistance was considered bordering, and for all other items the tour was suffering. It is concluded that the PLPP instrument is valid and reliable, able to identify in clinical practice the actions performed to prevent pressure injury in pediatrics, aiming to promote patient safety in the hospital environment.